2022
DOI: 10.1111/jocd.14906
|View full text |Cite
|
Sign up to set email alerts
|

Subject satisfaction and psychological well‐being with escalating abobotulinumtoxinA injection dose for the treatment of moderate to severe glabellar lines

Abstract: Background Previous studies indicate that the efficacy and durability of a single AbobotulinumtoxinA (ABO) treatment for moderate to severe glabellar lines may be enhanced with increasing dose, while safety outcomes remain consistent with those of the licensed dose (50 U). Aims Evaluation of subject‐reported indicators of treatment efficacy, satisfaction, and psychological well‐being with ABO dose escalation. Methods A Phase 2, 36‐week, multicenter, randomized, dose‐ranging, double‐blind, placebo‐controlled st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Fast improvement and long-term duration can mainly explain the high percentage of patients (98.2%) who declared to be “highly satisfied” compared to the 85% of “satisfied” or “very satisfied” patients reported in the literature [ 4 , 5 , 12 ]. Although assessment scales used in this study are different from those used in RCTs and no direct comparison can be done, in almost 40% of the patients the treatment results lasted for 6 months, a greater percentage of patients compared with the 27% reported in RCTs [ 4 , 5 ]; these results are of particular interest since our cohort included a high percentage of non-toxin treatment-naïve patients, while only toxin treatment-naïve patients had been included in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fast improvement and long-term duration can mainly explain the high percentage of patients (98.2%) who declared to be “highly satisfied” compared to the 85% of “satisfied” or “very satisfied” patients reported in the literature [ 4 , 5 , 12 ]. Although assessment scales used in this study are different from those used in RCTs and no direct comparison can be done, in almost 40% of the patients the treatment results lasted for 6 months, a greater percentage of patients compared with the 27% reported in RCTs [ 4 , 5 ]; these results are of particular interest since our cohort included a high percentage of non-toxin treatment-naïve patients, while only toxin treatment-naïve patients had been included in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, clinicians almost always decided to switch from the five-point to the three-point injection technique, reducing the overall amount of units injected in both botulinum toxin treatment-naïve and non-treatment-naïve patients, an approach not described in previous studies. Controlled clinical studies on the efficacy of botulinum toxin at decreasing/lower dose could be of interest, in addition to the existing data with escalating dose [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, if patients want to have obvious results that last longer, utilizing higher units with ABO toxin can be better. 30 It is also important to reveal any unrealistic expectations that patients may have, as these have to be clarified, and treatment may need to be canceled if there is disconcordance with what is expected versus what can be achieved. 31…”
Section: Patient Expectationsmentioning
confidence: 99%
“…5 Furthermore, studies leveraging patient-reported outcome (PRO) assessments after glabellar line treatment with BoNT/A have revealed benefits to patients' self-esteem, perception of age, and quality of life (QoL) across multiple dimensions. [6][7][8][9] LetibotulinumtoxinA, a proprietary formulation of purified 900 kDa Clostridium botulinum neurotoxin type A complex manufactured by Hugel, Inc. (Chuncheon, Republic of Korea) from strain CBFC26, is an investigational drug under review by the FDA and was recently shown to be well-tolerated and superior to placebo in reducing glabellar line severity posttreatment. 10 Its impact on psychosocial health-related QoL and subject satisfaction with treatment have yet to be fully reported.…”
mentioning
confidence: 99%
“…5 Furthermore, studies leveraging patient-reported outcome (PRO) assessments after glabellar line treatment with BoNT/A have revealed benefits to patients' self-esteem, perception of age, and quality of life (QoL) across multiple dimensions. 6–9…”
mentioning
confidence: 99%